The Relationship Between Knowledge on Nutrition and The Case of Anemia in Pregnant Women - Hermansyah, Anang; Danianto, Ario; Cholidah, Rifana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Anemia is a condition when the body's hemoglobin levels decrease. Hemoglobin serves as a carrier of oxygen throughout the body. Pregnant women are one of the populations most susceptible to anemia because their bodies' nutritional and physiological needs change throughout pregnancy. One factor influencing the occurrence of anemia in pregnant women is a lack of knowledge about nutrition during pregnancy. This study aims to determine the anemia case, the level of knowledge, and the relationship between the level of knowledge about nutrition and the anemia case in pregnant women. The type of research conducted is an observational analytical research with a cross sectional approach and uses Spearman rank data analysis with a sample size of 33 respondents. The results of the study showed that the anemia case was 63.6%, the level of knowledge of respondents was dominated by a low level of knowledge, and there was no relationship between the level of knowledge about nutrition and the anemia case in pregnant women with a significance value of 0.578% and had a weak relationship with a correlation value of 0.101%.